ALKBH5 gene polymorphisms and Wilms tumor risk in Chinese children: A five‐center case‐control study - Hua, Rui‐Xi (J Clin Lab Anal, 2020)
BACKGROUND: Wilms tumor is a frequently diagnosed renal cancer among children with unclear genetic causes. N6‐methyladenosine (m(6)A) modification genes play critical roles in tumorigenesis. However, whether genetic variations of m(6)A modification genes predispose to Wilms tumor remain unclear. ALKBH5 (AlkB homolog 5), a crucial member of m(6)A modification genes, encodes a demethylase that functions to reverse m(6)A RNA methylation. METHODS: Herein, we evaluated the association of single nucleotide polymorphisms (SNPs) in the m(6)A modification gene ALKBH5 and Wilms tumor susceptibility in a large multi‐center case‐control study. A total of 414 Wilms tumor cases and 1199 healthy controls were genotyped for ALKBH5 rs1378602 and rs8400 polymorphisms by TaqMan. RESULTS: No significant association was detected between these two polymorphisms and Wilms tumor risk. Moreover, 1, 2, and 1‐2 protective genotypes (rs1378602 AG/AA or rs8400 GG) did not significantly reduce Wilms tumor risk, compared with risk genotypes only. Stratification analysis revealed a significant relationship between rs1378602 AG/AA genotypes and decreased Wilms tumor risk in children in clinical stage I diseases [adjusted odds ratio (OR) = 0.56, 95% confidence interval (CI) = 0.32‐0.98, P = .042]. The presence of 1‐2 protective genotypes was correlated with decreased Wilms tumor risk in subgroups of age > 18 months, when compared to the absence of protective genotypes (adjusted OR = 0.74, 95% CI = 0.56‐0.98, P = .035). CONCLUSION: Collectively, our results demonstrate that ALKBH5 SNPs may exert a weak influence on susceptibility to Wilms tumor. This finding increases the understanding of the role of the m(6)A gene in tumorigenesis of Wilms tumor.